Solidarity economy and good living: points of (dis)connection (Emancipação, 2020)
In the wake of the various critical strands of modernity, we currently highlight the denunciation of the failures of projects anchored in the development paradigm. In this sense, there are several proposals that seek to promote, consolidate or systematize what would be alternatives to development. In this paper, we approach two notions that seek to consolidate themselves as concrete alternatives to modernizing development: the Solidarity Economy and Good Living. We present a brief bibliographical review of the notions and, following, a reflective effort on points of connection and disconnection between them. The preliminary perception is that, apart from differences, there is a field of strong congruences and interconnections, among which stand out the criticism and the search for overcoming the exclusionary and impersonal capitalism, which is characteristic of industrial modernity and which continues today. with characteristics characteristic of postmodern conditions in the countries of the global south.
Keywords: Postmodernity. Development. Alternatives.